THE RECRUITMENT SYSTEM OF EDUCATORS AND EDUCATION PERSONNEL AT ISLAMIC CENTER ELEMENTARY SCHOOL, SAMARINDA CITY - Bagus Setiawan; Miranti (re-JIEM (Research Journal of Islamic Education Management), 2024)
The recruitment system for quality educators is an important aspect of supporting the vision and mission of the school. However, in practice, the recruitment process is sometimes far from optimal. This study examines the recruitment system for educators and education staff, as well as the supporting and hindering factors at SD Islamic Center Kota Samarinda. The method used is field research with data collection techniques through observation, documentation, and interviews. The results show that the recruitment process at SD Islamic Center Kota Samarinda involves coordination with the foundation, preparation of guidelines, and strict selection to produce quality educators to support the school’s vision and mission. Supporting factors for recruitment include coordination with the foundation, setting standards for applicants, and strict selection, while the main obstacles are applicants who do not meet qualifications and lack discipline. This study is expected to serve as a reference for the educator recruitment system, help the school and foundation improve recruitment effectiveness, and provide policy guidelines for designing a recruitment process that meets the needs of educational institutions.